MODEL PEMBERDAYAAN KOMUNITAS TANGAN DI ATAS JENEPONTO TAKALAR GOWA (TDA JENTAGO) MELALUI PENGEMBANGAN INOVASI KEWIRAUSAHAAN DI KECAMATAN BAJENG KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
The subject matter is further described into several sub-problems, namely: first, how is the TDA Jentago community empowerment model through the development of entrepreneurial innovation, and what are the supporting and inhibiting factors of the TDA Jentago community empowerment model through entrepreneurship development in Bajeng District, Gowa Regency. The results of this study indicate that the TDA Jentago Community Empowerment Model through Entrepreneurship Innovation Development can be seen from the achievements in the implementation reality in the field: (1). Potential Development Intensity, (2) Fostering Social Spirit, (3) Competitiveness Enhancement Model, (4) Synergy Based on High Trust Community Principles, and (5) Creating Technology-Based Business Resource Centers. To determine the supporting and inhibiting factors of the Empowerment Model The TDA Community in community empowerment through Entrepreneurship Innovation by the TDA Jentago Community, namely: (1) Ease of sharing knowledge between members, (2) Extensive links, (3) not formal, while the inhibiting factor itself is the flexibility of members' time in community meetings.